Neurologic complications following treatment of canine hypoadrenocorticism - MacMillan, Karen L. (2003)
After treatment for hypoadrenocorticism, an 18-month-old dog exhibited marked ataxia and intermittent muscle tremors, progressing to head pressing, dysphagia, and quadraparesis. Serum sodium increased by 38.9 mmol in 48 hours, suggesting myelinolysis. The dog made a complete recovery after intensive treatment.